Practical aspects of coking in Cundinamarca y Boyacá - Romero-Balaguera, Segundo Manuel (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
Taking advantage of the excellent qualities of the studied coals from the coalfields in Cundinamarca and terms of the types of coking ovens, for excellent performance and quality that allows them to be very competitive.The international market is very demanding in terms of the quality of coke and CRI and CSR indexes, that is why coals laboratories were implemented and improved the system of sampling and analysis of laboratories for more agile and modern. Mixtures were made with the test methodology and empirical methods combining swelling index and rank cals were the theree main types: high, medium and low volatile. But with studies and techological change and enviromental control, process is managed, allowing the coke industry to serve as a development center for the promotion of industries in the central area of this country. In the study the whole process is presented beginning with the explotaitation of coking coals, the care that must be taken into account to mainttain good quality, transport and enviromental measures, the process of crushing and grinding to prepare the optimal mix and laboratory tests necessary to maintain quality control, the types of ovens in Boyacá Colombia, yields and advances in the se technologies, and finally, the system shutdown process. All of the above was addressed in order to add value to the product with the fulfillment of the international market standards.